DESK ORGANIZER YANG DILENGKAPI DENGAN SINAR ULTRAVIOLET UNTUK TELLER BANK - Gerardus Gladwin Pollot; Kresno Soelasmono; Brian Kurniawan Jaya; Wyna Herdiana (Indonesian Society of Applied Science, 2022)
With the COVID-19 pandemic, people are afraid to meet other people because they are afraid of getting infected, as well as people who work as tellers, where these tellers meet other people every day. In order to reduce the fear and worry of the people, the idea emerged to design a desk organizer equipped with ultraviolet-C where this ultraviolet-C light can also kill COVID-19 with a certain spectrum. The study was carried out by conducting interviews with several tellers and the conclusion was that there was still not much use of ultraviolet-C rays in banks to sterilize goods, where cleanliness of goods was very important during this COVID-19, the use of ultraviolet-C rays is still being used. to check the authenticity of the money. The innovation that he wants to produce is the use of ultraviolet-C rays that can sterilize goods where there are still not many uses of ultraviolet-C rays in banks. On the other hand, tellers also need a desk organizer so that the table is always neat, therefore the innovation is designed, namely a desk organizer equipped with a slot to sterilize goods using Ultraviolet-C rays with the aim of not only keeping the table tidy, it can also be used to disconnect the chain of spread of COVID-19 that can stick to goods.